Pentingnya Menabung Sejak Usia Dini di Sekolah Dasar 0723 Parmainan - Arfin Hasibuan; Irensi Nabila Nasution; Sakilah Nasution; Sarmadan Nasution; Mhd Sahputra Lubis (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the importance of saving from an early age at Parmainan 0723 Elementary School. The background of this study stems from the phenomenon of low interest in saving among elementary school children, who tend to be more interested in consumptive behavior than preparing for the future. The study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation with teachers, students, and parents. The results show that school savings programs play a significant role in developing a thrifty character, fostering discipline, and teaching financial management from an early age. Key supporting factors include teacher support, parental involvement, and easily accessible school savings facilities. However, obstacles were also identified, such as children's low understanding of the benefits of saving, the influence of a consumerist environment, and a lack of intensive outreach from the school. Savings programs packaged with creative methods, such as savings competitions or savings with prizes, have been shown to increase student participation. In conclusion, the habit of saving from an early age has a positive impact on children's character development, particularly in terms of discipline and financial planning. It is recommended that schools collaborate with banks or school cooperatives to provide more attractive savings facilities and actively involve parents in the process of fostering students' savings habits.